Integration of Spirituality and Psychology in Islamic Counseling Guidance - Taufiq Hidayat; Suryadi Fajri (Universitas PGRI SUMATERA BARAT, 2025)
Islamic Counseling Guidance (ICG) offers a holistic approach to address the limitations of Western psychology, particularly when dealing with issues that involve spiritual backgrounds. This study aims to integrate the concept of Islamic Counseling (ICG) with Western psychology to address modern challenges faced by Gen Z, including Fear of Missing Out (FOMO), self-diagnosed mental health, and hate speech. Through a qualitative method based on library research, the study analyzes various literatures to integrate ICG with Western psychology. The research highlights the importance of tazkiyatun nafs (purification of the soul) through practices such as dhikr (remembrance of Allah), repentance, and worship that engage the qalb (heart) and ruh (spirituality) as core solutions to problems. In contrast, Western psychology focuses on the nafs (self) and aql (intellect), using behavioral and cognitive therapies. The study’s findings suggest that this integration provides effective, holistic solutions, promoting inner peace and improving life quality in accordance with human nature. Future research should quantitatively assess the effectiveness of BKI on a broader population for generalizability across diverse social and cultural groups.